2012
DOI: 10.1097/acm.0b013e318253dcdb
|View full text |Cite
|
Sign up to set email alerts
|

Medical Student Self-Efficacy With Family-Centered Care During Bedside Rounds

Abstract: Purpose Factors that support self-efficacy must be understood in order to foster family-centered care (FCC) during rounds. Based on social cognitive theory, this study examined (1) how 3 supportive experiences (observing role models, having mastery experiences, and receiving feedback) influence self-efficacy with FCC during rounds and (2) whether the influence of these supportive experiences was mediated by self-efficacy with 3 key FCC tasks (relationship building, exchanging information, and decision making).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 45 publications
1
23
0
Order By: Relevance
“…Having role models who teach, and learn, in front of patients assists students in developing their own communication skills and bedside manner. 4 …”
Section: What Is Fcc?mentioning
confidence: 97%
“…Having role models who teach, and learn, in front of patients assists students in developing their own communication skills and bedside manner. 4 …”
Section: What Is Fcc?mentioning
confidence: 97%
“…When proper role modelling and feedback on learning are combined with sufficient opportunities for practical experiences, students may be assisted in developing their sense of self-efficacy and thus the patient-centred behaviour that they intend to perform. 25 Crucial aspects that therefore need to part of a patient-centred curriculum are several opportunities where students can observe and practice patient-centredness both in simulation and in the clinical areas. This should be followed by feedback and reflection opportunities.…”
Section: Discussionmentioning
confidence: 99%
“…36 Also, clinicians need to be instructed to involve the patient and family instead of just allowing presence, focus on the goals of care instead of just the interesting aspects of the case, and humanize the patient when conducting rounds with FP. 43 In a study of 36 parents, 19% reported feeling anxious during rounds, yet 83% reported improved satisfaction and 89% felt that they had improved information about their child's condition when allowed to be present on rounds. 11,[37][38][39][40] Furthermore, hallway rounds that do not include family members have been reported to increase anxiety and suspicion and also cause concerns about confidentiality, as evidenced by direct feedback from families to those testing models of FPR.…”
Section: Will the Information On Rounds Cause Families Undue Anxiety?mentioning
confidence: 99%